Giving Additional Food Snakehead Fish On The Weight Of Stunting Children At The Sadar Jaya Health Center UPT - Siti Khotijah; Ika Permanasari; Dilgu Meri; Tino Suhendro (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Stunting remains a significant nutritional issue in Indonesia, primarily caused by inadequate dietary intake. Nutritional deficiencies in toddlers often result from insufficient breastfeeding and a lack of proper nutrition from complementary foods. This study aims to evaluate the impact of supplementary feeding (PMT) made from snakehead fish on the nutritional status of stunted toddlers aged 24–47 months. The research employed a total sampling method, involving 15 toddlers within the specified age range. Prior to the intervention, the respondents had an average body weight of 10.77 kg, categorized as severely underweight. Following the administration of snakehead fish-based PMT, their average weight increased to 12.33 kg, falling into the underweight category. Statistical analysis revealed a p-value of 0.000, indicating a significant effect of the snakehead fish-based PMT in improving the nutritional status of stunted toddlers. These findings highlight the potential of local food sources, such as snakehead fish, to enhance maternal and child health efforts—particularly in addressing malnutrition through optimized use of locally sourced PMT in various preparations.